2021
DOI: 10.1093/fampra/cmab167
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient prescription patterns of COVID-19 drugs in the metropolitan area of Mexico City

Abstract: Background We aimed to describe the use of drugs with apparent efficacy in ambulatory patients with confirmed COVID-19 and the relationship of Google Trends searches with prescriptions and the total number of COVID-19 cases in Mexico City. Methods Between March 2020 and February 2021, we surveyed 350 patients confirmed to have COVID-19 across 3 hospitals in Mexico City for their ambulatory prescriptions. We analysed the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…During the COVID-19 pandemic, increasing prescription and self-medication of off-label drugs with unproven efficacy and safety to treat this disease has been described in many countries. [13][14][15] In our study, the frequency of ivermectin consumption in the Chincha province was 67.2%, with more than 50% self-medicating and 43.5% obtaining the drug by medical prescription.…”
Section: Discussionmentioning
confidence: 53%
“…During the COVID-19 pandemic, increasing prescription and self-medication of off-label drugs with unproven efficacy and safety to treat this disease has been described in many countries. [13][14][15] In our study, the frequency of ivermectin consumption in the Chincha province was 67.2%, with more than 50% self-medicating and 43.5% obtaining the drug by medical prescription.…”
Section: Discussionmentioning
confidence: 53%
“…Although medication use may have been underreported in a minority of cases, the present study demonstrated that the use of repurposed drugs was largely evidence-based because unauthorized medication use was highly limited in 2020. This situation was in contrast to that in other countries, where repurposed drug use of ivermectin or hydroxychloroquine (inexpensive oral medications) was relatively common [33][34][35]. In some countries, these drugs were proposed as therapeutic options, such as the emergency use authorization of hydroxychloroquine in the United States (which was subsequently revoked) [36].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that the prescription of non-evidence-based medications for the treatment of COVID-19 is frequent, ranging from 28 to 29% [ 42 , 43 ]. Furthermore, a previous study evaluated the factors influencing medication prescription for COVID-19 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%